Homogeneous eigenvalue problems in Orlicz-Sobolev spaces - Bonder, Julián Fernández; Salort, Ariel; Vivas, Hernán (Topological Methods in Nonlinear Analysis, 2023)
In this article we consider a homogeneous eigenvalue problem ruledby the fractional $g$-Laplacian operator whose Euler-Lagrange equation is obtained by minimization of a quotient involving Luxemburg norms.We prove existence of an infinite sequence of variational eigenvaluesand study its behavior as the fractional parameter $s\uparrow 1$ amongother stability results.